Properties of Isolated Lignin From Model Wastewater (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Model wastewater, imitating the hydrothermal treatment of birch wood in the basins of veneer production, was obtained under laboratory conditions. Birch lignin (BLIG) was isolated from the model wastewater by precipitation with concentarted sulphuric acid. The increase in reduced viscosity with decreasing concentration of BLIG in the water solutions indicated its polyelectrolyte behaviour. The presence of both ionized functional groups and hydrophobic aromatic fragments in the BLIG molecules favoured its surface active properties. With decreasing pH and increasing concentration, the surface activity of BLIG at the air-water and oil-water interfaces increased, indicating the enhanced hydrophobicity of lignin fragments due to the protonization of its acidic groups. The pronounced surface activity of BLIG was in accordance with the very low value of its critical micelle concentration. The dependence of the emulsion stability on the ionic strength may testify the predominant structural mechanical mechanism of the stabilization of the rapeseed oil-in-water emulsion, containing BLIG as a stabilizer. The revealed surface properties of the isolated lignin allow predicting its application for lowering surface tension in different disperse systems to prevent the coalescence and agglomeration phenomena.